2008
DOI: 10.1080/09638280701192949
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of sex differences in work injuries: Implications for primary care practice

Abstract: Women and men differ in terms of work injury circumstances and factors contributing to post-injury outcomes. Primary care providers should consider sex when evaluating and treating work-injured adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, while men were much more likely than women to sustain fatal and/or severe wrTBI, this gap narrowed when milder injuries were examined. This suggests that men and women may differ regarding work exposures and, subsequently, circumstances and severity of injury [Harrold et al, ]. However, further investigation is needed to inform sex‐specific prevention strategies, as the majority of wrTBI studies included a small number of females and did not stratify results by sex.…”
Section: Discussionmentioning
confidence: 99%
“…However, while men were much more likely than women to sustain fatal and/or severe wrTBI, this gap narrowed when milder injuries were examined. This suggests that men and women may differ regarding work exposures and, subsequently, circumstances and severity of injury [Harrold et al, ]. However, further investigation is needed to inform sex‐specific prevention strategies, as the majority of wrTBI studies included a small number of females and did not stratify results by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Women have been less likely to belong to a workforce union for support than are men, a consistent trend from 1983 to 2011 (Bureau of Labor Statistics, 2012). Studies also reveal gender inequality in the process of claiming compensation for work leave (Harrold, Savageau, Pransky, & Benjamin, 2008). It has been suggested that gender inequality does not come from state laws or policies; rather, medical and rehabilitation practitioners, as well as trade unionists, have been identified as making compensation and RTW less beneficial for women (Guthrie & Jansz, 2006).…”
Section: Gender Issuesmentioning
confidence: 99%
“…Ten articles were retrieved [Zimmerman et al, 2004; Cifuentes et al, 2007, 2008a Grandey et al, 2007; Meyer et al, 2007; d'Errico et al, 2007; Alterman et al, 2008; Bell et al, 2008; Forstmeier and Maercker, 2008; Ward et al, 2008], from which reference lists were reviewed to identify other relevant studies [Glomb et al, 2004; Hadden et al, 2004; Shaw and Gupta, 2004; Liu et al, 2005]. Additional published [Zhang and Snizek, 2003; Pransky et al, 2005a,b; Crouter et al, 2006; Lis et al, 2007; Verma et al, 2007; Benjamin et al, 2008; Dierdorff and Ellington, 2008; Harrold et al, 2008]. Unpublished materials [Huzyak, 2008; Spreng, 2008; Boyer et al, in press; Gardner et al, submitted] were found through the O*NET webpage (http://www.onetcenter.org/dl_files/omb2008/AppendixE.pdf), web search engines (e.g., Google), and personal communication with researchers known to have conducted research using O*NET.…”
Section: Methodsmentioning
confidence: 99%